Nitric oxide production in murine spleen cells: role of interferons and prostaglandin E2 in the generation of cytotoxic activity - Dominique Vaillier; Richard Daculsi; Norbert Gualdel (Mediators of Inflammation)
The production of nitric oxide (NO) was measured in cultures of spleen cells stimulated by lipopolysaccharide (LPS), IL-2 or LPS + IL-2. We observed that NO synthesis is increased by IFN-γ but inhibited by IFN-α/β. This is not the case when IL-2 is present in the cultures, since interferons play a minor role in the regulation of the NO production. When IL-2 and LPS were associated in the cultures, the IFN-α/β role seems more important than that of IFN-γ. PGE2 inhibits NO production in LPS supplemented cultures but has a slight effect in the presence of IL-2 and no effect with IL-2 + LPS. 3-isoButyl-1-methylxanthine (IBMX), an inhibitor of phosphodiesterases, induces a decrease of IFN production. In the presence of H-7, an inhibitor of protein kinase C (PKC), NO production is reduced when the cultures are supplemented by LPS or IL-2 but not when IL-2 and LPS are both added. H-7 also reduced IFN production. In the presence of NG-monomethyl-L-arginine (N-MMA), an inhibitor of NO synthesis, IFN production was increased, with no change in the cytotoxic activity. Hence, interferons regulate NO production by mouse spleen cells and, in return, NO modulates the generation of IFN.